TRANSLATION PROCEDURES OF MISSION IMPOSSIBLE: ROGUE NATION MOVIE SUBTITLE - Cicih Nuraeni; Mohamad Aditya Pratama (Leksema: Jurnal Bahasa dan Sastra, 2019)
The objective of this research is describing on translation procedures which used for the government and covert institution terms in Mission Impossible: Rogue Nation movie subtitle by the official subscene translator. Translation procedures are the inseparable aspects within translation process which determine their end-result delivered for target reader rightly. The researchers applied Newmark’s theory for subtitle analysis. By the process of analysis, it was found that there were 16 of 18 types of translation procedures which could be categorized into two specifications. The frequently procedures found were literal translation, transference, modulation, and shift or tranposition. In addition, the relevant procedures of specific terms were cultural equivalence, functional equivalence, through translation, and paraphrase.